The effects of social identity and social identity content on cohesion, efficacy, and performance across a competitive rugby league season - Evans, A. L.; Coffee, P.; Barker, J. B. (International Journal of Sport and Exercise Psychology, 2023)
Social identity (one's sense of belongingness to a group) and social identity content (what it means to belong to a group) are important psychological constructs for cognition and behaviour. Whilst some longitudinal social identity research exists, researchers have yet to explore the temporal effects of social identity content in sport. Across a competitive season, we therefore explored the main and interactive effects of social identity and two types of social identity content (results and friendships) on cohesion, self and team-level efficacy, and subjective team performance. Participants were 167 male rugby league athletes (Mage = 18.16 ± 0.44 years) drawn from all eight teams competing in a single English Premier Rugby League Division. At the start, middle, and end of their nine-week season, participants completed a series of measures. Multilevel modelling analyses found that social identity significantly and positively predicted all study outcomes amongst athletes, and self and team-level efficacy across time. As athletes` social identity strengthened across the season, so too did self and team-level efficacy. Also at the time-level, the interaction between social identity and friendships content significantly and positively predicted team-level efficacy. In other words, social identity was important for team-level efficacy throughout the season when friendships content was high. Overall, our findings suggest that social identity is important for cohesion, efficacy, and team performance. The lack of interaction effects between social identity and results/friendships contents may be attributable to athletes adopting social creativity by altering the importance placed on results and friendships throughout the season.